Superantigen staphylococcal enterotoxin B-induced T-helper cell activation is independent of CD4 molecules and phosphatidylinositol hydrolysis. - Oyaizu, N (1992)
The role of the CD4 molecule in activation of T-helper cells was examined by investigating the effect of an anti-CD4 monoclonal antibody (Leu3a) in conventional peptide antigen-specific cloned T-helper cells that are also reactive to staphylococcal enterotoxin B (SEB). These T-helper cell clones are CD4+/CD45RO+/T-cell antigen receptor beta-chain variable region 12-positive and can respond to nominal peptide antigens and SEB by proliferation in the presence of class II major histocompatibility complex-expressing accessory cells. Although antigen and SEB were comparable in their ability to induce proliferative responses, interleukin 2 (IL-2) production, and IL-2 receptor alpha-chain expression, stimulation with SEB failed to trigger phosphatidylinositol hydrolysis or a rise in the intracellular free calcium ion concentration. Leu3a treatment inhibited antigen-induced proliferative responses of T cells with concomitant suppression of IL-2 production and IL-2 receptor expression. In contrast, SEB-induced responses were unaffected by Leu3a. These findings indicate that the functional consequences of binding (ligation) of conventional antigen and of superantigen with the T-cell receptor are distinct in the context of both signal transduction pathways and participation of CD4 molecules.